1995
DOI: 10.1152/jappl.1995.79.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Combined hypoxia and hypercapnia evokes long-lasting sympathetic activation in humans

Abstract: We studied ventilatory and neurocirculatory responses to combined hypoxia (arterial O2 saturation 80%) and hypercapnia (end-tidal CO2 + 5 Torr) in awake humans. This asphyxic stimulus produced a substantial increase in minute ventilation (6.9 +/- 0.4 to 20.0 +/- 1.5 l/min) that promptly subsided on return to room air breathing. During asphyxia, muscle sympathetic nerve activity (intraneural microelectrodes) increased to 220 +/- 28% of the room air baseline. Approximately two-thirds of this sympathetic activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
201
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(224 citation statements)
references
References 0 publications
17
201
2
4
Order By: Relevance
“…[4,5] Morgan et al demonstrated in healthy volunteers that hypoxic hypercapnia leads to a protracted increase in MSA, whereas hyperoxic hypercapnia only transiently increases sympathetic activity indicating that hypoxemia is responsible for the effect. [40] Chronic intermittent hypoxia has thus clinically relevant prolonged effects on blood pressure in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] Morgan et al demonstrated in healthy volunteers that hypoxic hypercapnia leads to a protracted increase in MSA, whereas hyperoxic hypercapnia only transiently increases sympathetic activity indicating that hypoxemia is responsible for the effect. [40] Chronic intermittent hypoxia has thus clinically relevant prolonged effects on blood pressure in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of ventilation or blood gases may also have caused modulations in MSNA during the different cold stimuli (Hardy et al, 1994;Morgan et al, 1995). In our study, respiratory movements were monitored with a strain gauge strapped around the chest with a rubber band to control the inadvertent apneas and irregular breathing.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The mechanisms implicated in this phenomenon are still unclear. Firstly, it has been hypothesized that the effect of sympathetic excitation induced by hypoxia might persist for a long time, also during normo-oxygenation conditions (28,29). Secondly, a potentiation of peripheral chemo-reflex responses has been detected in OSA subjects, possibly contributing to maintain a tonic sympathetic excitation during wakefulness (27,30).…”
Section: Sleep Breathing Disorders and Ansmentioning
confidence: 99%